Investigating the mental health of agriculture teachers in the Midwest - Wippel, Macie Taylor (Kansas State University, 2023)
Mental health awareness has increased throughout the last decades. What used to be seen as a negative connotation, mental health is evolving to be less stigmatized by society. Mental health illnesses can be mild or extreme and can be a multitude of different illnesses. Identifying and addressing mental health illnesses is important to the overall lifestyle of a person. There has been a historical rise in teachers exiting the classroom creating a nationwide teacher shortage. In agricultural education, there has been a constant shortage and need for quality teachers in the profession. Agricultural education teachers have job duties that go beyond the classroom and have unique stressors in their profession. This study investigates: (1) areas within the school environment that impact the mental health of agricultural education teachers, (2) the individual experiences that have caused the most stress and/or anxiety to teachers in the agricultural education profession, and (3) how personal feelings and/or emotions are impacted by the school environment and experiences in the profession. This study involved survey methods to disseminate a survey to agricultural education teachers in the Midwest. Of the random sample, 57 complete questionnaires were returned. The responses included both male and female agriculture teachers of different ages and career lengths. The instruments used in this survey investigated the school environment, daily stressors, and depression symptoms of teachers. Agriculture teachers have roles and responsibilities beyond the classroom and the workload is causing increased levels of stress and depression. It is important for the future of the agricultural education profession to identify stressors impacting the mental health of the agriculture teacher.
Keywords: Agricultural education; Mental health; Agriculture teachers